The need for establishment of a family court in Malaysia: an appraisal - Che Soh @ Yusoff, Roslina; Mohd Arshad, 'Ain Husna (International Islamic University Malaysia, 2013)
The adjudication of family disputes by different courts with different jurisdictions in the present court system is ineffective in providing a comprehensive approach to the management of family-related disputes. Furthermore, the adversarial system of litigation of the present courts in Malaysia negates the possibility of resolving conflicts amicably. The establishment of a family court in Malaysia would be in line with the objective of the National Family Policy which encourages the sustainability of the family institution. Basically, this paper seeks to discuss the concept of family court and the need for its establishment in Malaysia. The paper will also briefly discuss the implementation of family court systems in Australia, Singapore and Egypt as these countries have a well developed family court system. The purpose is to learn from their experiences in providing a comprehensive solution to resolve family related disputes in Malaysia.